Crustal structure and tectonic evolution of Greater Maldive Ridge, Western Indian Ocean, in the context of plume-ridge interaction - Kunnummal, Priyesh; Anand, S.P. (My University, 2022)
The Greater Maldive Ridge (GMR), consisting of the Maldive Ridge (MR) and Deep Sea Channel (DSC) region, is the N-S trending, middle segment of Chagos-Laccadive Ridge system. This ridge system is widely considered to be the repository representing the interaction between Central Indian Ridge spreading centre and Reunion plume. The present study investigates in detail, spatial variations in effective elastic thickness (Te ), isostasy and crustal structure of GMR using high resolution satellite derived gravity, residual geoid and bathymetry data. Estimated T e values along the GMR from 2D and 3D flexural modelling ranges from 6.5–16.5 km with comparatively lower T e values over MR (7–9 km) and slightly higher values over the DSC region (>10 km). Geoid to Topography Ratio computed for two wavelength bands shows almost similar kind of variation along the ridge with a maximum value of 1.4 m/km in the DSC region, decreasing northwards to 0.6 m/km over MR. Integrating results from the present study with crustal thickness, Moho undulations and Curie depth along the entire length of the GMR suggest that MR was formed in the vicinity of spreading centre while DSC region was under a long transform fault which has given rise to the gap zone between Chagos Bank and Maldive Ridge during plume-ridge interaction.
Keywords: Plume-ridge interaction; Maldive ridge; Geoid to topography ratio; Effective elastic thickness; Satellite derived free-air gravity; Curie depth